Assessment of Soil Fertility Characteristics of Chemical-Fertilized Banana Fields of South India. Issue 3 (4th February 2019) - Ray, J. G.; Nidheesh, K. S.
ABSTRACT: Soil fertility status of continuously cultivated, chemical-fertilized banana fields of the south Indian states, Kerala, Karnataka, and Tamilnadu, in relation to seasons and varieties is assessed. The major goals were to identify soil types in terms of soil fertility characteristics and specific banana varieties of the region. The focus was to assess specific soil parameters favoring specific varieties, if any, towards global applications. Altogether 286 soil samples collected at random from 143 fields of 13 cultivated varieties, representing 47 different soil series in two seasons, are analyzed and compared. Soil pH and nutrient parameters of different banana variety cultivated fields remained significantly different. Total phosphorus and potassium content of these soils remained normal, but soil nitrogen content was low. The investigation remains a good model for the inventory of specific soil types, soil nutritional characteristics, and ecological amplitude of specific crop of high varietal diversity over a broad area.